Identify indicators of climate change through the analysis of the amount of rain in Iraq (Journal of the College of Education for Women, 2019)
United nation determined many basic climatic effects which affect the crust of Earth.And the most important one is the climatic change and its effect on environmental, economic,social, and political effects. So, the amount of rain which is considered as one of climaticchanges in Iraq should be studied.So, this research explains the factors which affect rain, itsoverall average, the variation in the amounts of rain, the amount of yearly rain and variationin both yearly and monthly rains by using standard variation and yearly fluctuation.As aresult, it is concluded that the number of rainy days doesn't mean an increase in rains amount.And there's variation in rains amount in all study areas which is contrastive from one stationto another.